Opening Up: How Centralization Affects Participation and Inclusion in Strategy Making. Issue 3 (June 2017) - Mack, Daniel Z.; Szulanski, Gabriel
Abstract : Despite the benefits of opening the strategy process, greater inclusiveness and transparency stand in sharp contrast to the conventional emphasis on elitism and opacity in strategy making, especially in centralized organizations where decision making is driven by top management. We suggest that centralized organizations can manage this tension by combining participatory and inclusive practices. Whereas participation is about increasing stakeholders' input for decisions, inclusion is about creating and sustaining a community of interacting stakeholders engaged in an ongoing stream of issues in the strategy process. We show that the distinction between participatory and inclusive practices helps to explain why and how centralized and decentralized organizations engage with stakeholders differently over the two phases of alternatives generation and idea selection in the strategy process. We illustrate our arguments using vignettes of the strategizing process at two public companies.